Customers’ Attitudes Towards the Use of Heat Pumps - Nikolić-Ristić, Dragana; Đokić, Nenad (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Modern society has recognized the need for harmony between rapid economic growth and the rational use of natural resources, bringing the concept of sustainable development into the focus of interest of the scientific and professional public. Respect ?? the concept of sustainable development and the transition from traditional to renewable energy is conditioned by the need for customers to achieve a high level of environmental awareness in order to view renewable energy use and energy-efficient behavior as a voluntary lifestyle rather than an imposed behavioral obligation. The existence of customer awareness about the possibilities of using renewable energy sources is the basis for changing the attitude of customers towards environmental protection and sustainable development. Customers’attitudes represent an important psychological determinant that has a significant impact on customers’ relation toward energy-saving behavior. The subject of research in this paper is customer attitudes in the context of renewable energy use. The aim of the paper is to analyze the attitudes of customers towards the use of heat pumps. Survey data were collected through a personal interview, while the measurement of customers’ attitudes towards heat pumps was performed on the basis of obtained ratings on a five-point Likert scale. The first part of the paper presents an overview of previous research in the scientific and professional literature, while the second part presents the results of an empirical study on the attitudes of customers towards the use of heat pumps in the Republic of Serbia.